Innate Immune Response in Brain, NF-Kappa B Signaling and Cystatins - Kopitar-Jerala, Nataša (Frontiers in Molecular Neuroscience, 2015)
Recently several reports have demonstrated that innate immune response and inﬂammation have an important role in major neurodegenerative diseases. The activation of the NF-κB family of transcription factors is a key step in the regulation of pro inflammatory cytokine expression. Microglia and other cell types in the brain can be activated in response to endogenous danger molecules as well as aggregated proteins and brain injury. During the past couple of years several studies reported the role of cystatins in neuroinflammation and neurodegeneration. In the present review I will summarize and analyze recent findings regarding the role of cystatins in inflammation and NF-κB activation. Type I cystatin stefin B (cystatin B) is an endogenous cysteine cathepsin inhibitor localized in the cytosol, mitochondria and nucleus. Mutations in the gene of stefin B are associated with the neurodegenerative disease known as Unverricht-Lundborg disease and microglial activation plays an important role in the pathogenesis of the disease. Stefin B deficient mice have increased caspase-11 expression and secreted higher amounts of pro-inflammatory cytokines. The increased caspase-11 gene expression, was a consequence of increased NF-κB activation